2007
DOI: 10.1002/cne.21426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of connexins in embryonic mouse neocortical development

Abstract: During embryonic development, young neurons migrate from the ventricular zone to the cortical plate of the cerebral cortex. Disturbances in this neuronal migration have been associated with numerous diseases such as mental retardation, double cortex, Down syndrome, and epilepsy. One possible cause of these neuropathologies is an aberration in normal gap junctional communication. At least 20 connexin (Cx) genes encode gap junction proteins in mice and humans. A proper understanding of the role of specific conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 93 publications
(123 reference statements)
4
71
0
3
Order By: Relevance
“…Furthermore, we found that Cx43 expression is closely associated with the radial glia and the migrating neurons (Cina et al, 2007), suggesting that Cx43 might play a significant role in the interactions between migrating neurons and the radial glial scaffold.…”
Section: The C-terminal Domain Of Cx43 Is Required For Neuronal Migramentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, we found that Cx43 expression is closely associated with the radial glia and the migrating neurons (Cina et al, 2007), suggesting that Cx43 might play a significant role in the interactions between migrating neurons and the radial glial scaffold.…”
Section: The C-terminal Domain Of Cx43 Is Required For Neuronal Migramentioning
confidence: 81%
“…Western blot analysis on embryonic brain tissue was conducted as described previously (Cina et al, 2007). Briefly, protein was isolated from cerebral cortices of E18 mice using radioimmune precipitation lysis buffer (50 mM Tris-HCl, pH 8.0, and 1% IGEPAL) supplemented with Mini Complete protease inhibitors (Roche Applied Science) and phosphatase inhibitors (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx are the gap junction-forming proteins of vertebrates and are encoded by a multigene family consisting of at least 20 different genes (61). There are several Cx genes expressed in the CNS during development including Cx26, Cx32, and Cx43 (46,(62)(63)(64). In rodents, Cx43 is expressed throughout development and is important for neuronal migration (46).…”
Section: +mentioning
confidence: 99%
“…These gap junction- and Talhouk et al, 2008 [19] ). [36] ; hypothalamus, inferior hippocampus, locus coeruleus, thalamus, superior colliculi [37] Astrocyte Locus coeruleus [38] ; perivascular, sub-pial, subependymal areas and brain parenchyma [39] ; subcortical areas [37] Cx29 Oligodendrocyte Oligodendrocytes, Schwann cells, paranodes and juxtaparanodes [38,40] Cx30 Astrocyte Mature grey matter [23] Cx32 Neuron Neuronal population in brainstem, cerebral cortical layers, substantia nigra [41] Oligodendrocyte Soma and processes of myelinated fibers [42] Cx36 Neuron Inferior olivary complex and other brainstem nuclei, cerebellum, mesencephalon, hypothalamus, thalamus, habe nular nuclei, pineal gland, Basal ganglia, septum, basal forebrain, amygdala and piriform cortex, hippocampal formation, cerebral cortex, olfactory bulb [43] ; locus coeruleus [44] Oligodendrocyte Primary cultures of rat brain oligodendrocytes [45] Microglia Microglial cultures from human and mouse [46] Cx37 Neuron Developing cortex of mice [47] Cx40 Astrocyte Temporal cortex [48] Cx43 Neuron Cerebral cortex [36] ; hippocampal neuronal subpopulation [49] Astrocyte Brain parenchyma [27] ; cortical [50] and subcortical regions [41] Microglia Diffuse cytoplasmic localization, and at interfaces between activated microglial cells [8] ; brain stab wounds [8] Cx45 Neuron Cerebral cortex, hippocampus and thalamus [51,52] ; olfactory nerves [53] Astrocyte Temporal cortex [48] Oligodendrocyte Soma and proximal processes of oligodendrocytes [54,55] Cx46 Astrocyte Cultured mouse astrocytes [48] Cx47 Neuron Cerebellum [56] Astrocyte In and around demyelinated areas [57] Oligodendrocyte Highly myelinated CNS tissues and few calcium-bindi...…”
Section: Gap Junctions In the Brainmentioning
confidence: 99%